2020
DOI: 10.1007/978-3-030-43887-6_32
|View full text |Cite
|
Sign up to set email alerts
|

Mining Human Mobility Data to Discover Locations and Habits

Abstract: Many aspects of life are associated with places of human mobility patterns and nowadays we are facing an increase in the pervasiveness of mobile devices these individuals carry. Positioning technologies that serve these devices such as the cellular antenna (GSM networks), global navigation satellite systems (GPS), and more recently the WiFi positioning system (WPS) provide large amounts of spatio-temporal data in a continuous way. Therefore, detecting significant places and the frequency of movements between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Although user movements are constrained by road or sidewalk networks, the trajectories can present dynamic and arbitrary shapes with respect to the individuals' needs. Following this idea, we cluster the SPs by using the method proposed by Andrade, Cancela, and Gama (2020). This approach proved to be more suited for identifying locations and find the most significant locations based on the frequency of visits/stops.…”
Section: Clustering Resultsmentioning
confidence: 99%
“…Although user movements are constrained by road or sidewalk networks, the trajectories can present dynamic and arbitrary shapes with respect to the individuals' needs. Following this idea, we cluster the SPs by using the method proposed by Andrade, Cancela, and Gama (2020). This approach proved to be more suited for identifying locations and find the most significant locations based on the frequency of visits/stops.…”
Section: Clustering Resultsmentioning
confidence: 99%
“…Um conceito que vem surgindo nos últimos anos é o de "turismo inteligente", como um componente de uma Smart City [Tripathy et al 2018], contemplado com a aplicação de ferramentas e abordagens inovadoras de tecnologias de informação para sua evolução contínua. Para tal, conforme [Andrade, Gama and Cancela 2019], existe uma riqueza de infraestruturas tecnológicas fornecendo grandes quantidades de dados espaço-temporais alimentando continuamente, em tempo real, enormes repositórios de dados de mobilidade humana que estão associados a muitos aspectos da vida contemporânea. Ainda, segundo [Xu et al 2021], dados de mobilidade turística podem ser vinculados a abordagens de ciência de dados para melhor compreender os destinos turísticos e suas interações.…”
Section: Estudo De Caso: Turismo Inteligenteunclassified
“…Smartphone data offer standardized, objective measures of participants' locations and movement patterns which may be useful in corroborating the findings of existing research on adolescents' daily lives. Previous research has demonstrated that human mobility patterns can be reliably measured using GPS data (Andrade et al, 2019) and that such patterns are meaningfully related to personality and daily activities in adolescence and young adulthood. Several studies have reported relationships between daily mobility patterns and personality traits in adolescence and young adulthood (Ai et al, 2019;Alessandretti et al, 2018;Stachl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%